The Approach Of Restorative Justice Theory In Resolving The Rohingya Case In Myanmar And The Syrian Conflict - Sutrisno, Andri; Hutabarat, Feby Amalia; Jaedin; Abdul Mutalib; Abdullah, Rahmat Hi (Jurnal Rechten : Riset Hukum dan Hak Asasi Manusia, 2024)
This article examines the application of restorative justice theory as an alternative approach to resolving human rights violations in two complex conflicts: the Rohingya crisis in Myanmar and the Syrian civil war. Both cases highlight the limitations of international legal frameworks and retributive justice in addressing large-scale violations, including genocide, forced displacement, and systemic discrimination. Restorative justice, emphasizing victim recovery, offender accountability, and community reconciliation, offers a more inclusive and sustainable solution to these crises. In Myanmar, the Rohingya community has faced decades of systemic persecution, culminating in military operations in 2017 that forced over 700,000 people to flee, primarily to Bangladesh. In Syria, the prolonged civil war since 2011 has caused widespread displacement and destruction, leaving over 8.6 million people internally displaced by 2022. Traditional mechanisms, such as International Court of Justice (ICJ) proceedings and United Nations interventions, have been hindered by political obstacles and enforcement challenges. This study explores the potential of restorative justice in both contexts, focusing on mechanisms such as inclusive dialogues, reparations, and reconciliation. Drawing on theoretical frameworks by Howard Zehr, Johan Galtung, and John Braithwaite, the article proposes practical applications for rebuilding trust and addressing the root causes of the conflicts. The findings suggest that restorative justice can not only address the immediate needs of victims but also foster long-term peace and stability by transforming social relationships and reducing the likelihood of recurrent violence. By shifting the focus from punitive measures to holistic recovery, this approach offers valuable insights into the resolution of modern humanitarian crises..